WORK RELATED FACTORS AND THEIR ASSOCIATION WITH FOOT AND ANKLE PAIN AMONG NURSES IN INTENSIVE CARE UNITS IN KARACHI, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
BACKGROUND: Ankle and foot pain is common among ICU nurses due to prolonged standing, walking, and physically demanding tasks such as patient handling and airway management. This pain results from musculoskeletal strain, poor posture, inappropriate footwear, and limited rest. ICU nurses are at higher risk compared to others due to repetitive movements, awkward positions, and long shifts with minimal breaks. Psychosocial stress, high workloads, and lack of support further increase vulnerability. Studies report a prevalence ranging from 23% to 51.8% globally. This study aims to assess the prevalence and work-related factors contributing to foot and ankle pain in ICU nurses.OBJECTIVE: The objective of this study was to determine the work-related factors and their association with foot and ankle pain among nurses in intensive care units in KarachiMETHODOLOGY: An observational cross-sectional study included 201 intensive care nurses from various hospitals across Karachi. Data was collected using Nordic Musculoskeletal Questionnaire (NMQ) and Manchester Foot Pain Questionnaire (MFPQ).RESULT: Out of 201 ICU nurses, 85.1% believed their job contributed to foot and ankle musculoskeletal problems. A high prevalence of pain was reported, with 86.1% experiencing foot/ankle pain in the last 12 months. Notably, 68.7% had taken sick leave, and 68.2% had sought medical treatment for their symptoms. The Manchester Foot Pain and Disability Index revealed that 30.3% experienced pain most of the time and 31.8% reported it some of the time. Pain significantly affected daily functioning: 39.8% avoided walking long distances, 39.3% changed their walking style, and 42.8% avoided prolonged standing. Chi-square analysis showed a statistically significant association between reported foot/ankle problems and avoidance of standing for long periods (p = 0.000). These results indicate a strong link between ICU work conditions and foot/ankle discomfort, leading to notable physical limitations.